Peningkatan Perilaku Sleep Hygiene Untuk Mencegah Gangguan Tidur Pada Remaja Di SMKN 4 Negara - Ni Luh Agustini Purnama; Selly Omega Dila Teju; Lusia Dwi Sri Wahyuni (Universitas Baiturrahim, 2026)
Sleep disorders are a problem experienced by teenagers at SMKN 4 Negara.Teenagers say that they only sleep for about 5 hours a day. They also mention that their pre-sleep habits or when they have trouble falling asleep include using their phones, even placing their phones on the bed while they sleep. They reveal that sometimes they stay online until late at night, whether it’s playing games, watching movies, or engaging in social media activities, which leads to difficulty sleeping and restless sleep, resulting in feeling unrefreshed and even dizzy upon waking up in the morning. The objective of this community service initiative is to assist students in enhancing their knowledge and strategies to improve sleep hygiene, thereby preventing sleep disorders among adolescents. Efforts to enhance adolescents' knowledge of proper sleep hygiene through health education and guidance are implemented to monitor students in carrying out the initiatives undertaken. The target audience for this community service activity is the 33 students at SMKN 4 Negara. Health education activities were conducted online via zoom meetings using audiovisual materials and booklets, followed by mentoring over a four-week period. Based on the results of pre-test and post-test evaluations, there was an improvement in knowledge and sleep hygiene behavior to prevent sleep disorders among adolescents